KEMUNGKINAN IMPLEMENTASI SISTEM PENGENDALIAN INTERNAL BERBASIS COSO FRAMEWORK PADA UNIT LAYANAN PENGADAAN POLITEKNIK NEGERI BATAM - Danar Irianto Irianto (Pusat P2M Politeknik Negeri Batam, 2020)
This research describes the evaluation of the implementation of an internal control system based on the COSO framework in the Batam State Polytechnic procurement unit. By using the COSO framework as outlined in the Internal Control Questioner based on 5 components and broken down into 17 COSO principles; (1) Control environment, (2) Control activities, (3) Risk assessment, (4) Information and communication, (5) Monitoring. Based on the research that has been done, there are several conclusions drawn. First, in the Control environment component, the procurement service unit is quite possible to implement a COSO-based control system. Secondly, the Risk assessment component of the procurement service unit is quite possible to implement a COSO-based control system. Third, the Control activities component of the procurement service unit is quite possible to implement a control system based on COSO. Fourth, the procurement service unit's Information and communication component is quite possible to implement a COSO-based control system. Fifth, the Monitoring component of the procurement service unit is not possible to implement a COSO-based control system. So as a whole it can be concluded that the Batam State Polytechnic procurement service unit is quite possible to implement a COSO-based control system.